THE EFFECT OF LEARNING CYCLE 5 E LEARNING MODEL IMPLEMENTATION ON FIFTH GRADE STUDENTS’ SCIENCE PROCESS SKILLS - Ani Satu Sapipah; Kartini Kartini; Vidya Setyaningrum (Universitas Majalengka, 2024)
This study aims to describe the effectt of applying the Learning cycle 5 E learning model on the science process skills of students on the material of the respiratory system in humans. The research design used is a Quasi Experimental type experiment with a nonequivalent control group design. The population in this study were all MIN 2 Pontianak Grade 5 students. Using purposive sampling technique, based on recommendations by the madrasah, namely class 5 C (control) and 5 E (experimental). Based on the results, it can be proven that: 1) Science process skills in the control class obtained a good category on the pretest, and on the posttest obtained a good category. 2) Science process skills in the experimental class obtained a good category on the pretest, and on of the posttest obtained a good category 3) Based on the results of hypothesis testing, it can be concluded that there is a difference between the control class and the experimental class with the effect size test results of 0.618, meaning that the application of the 5 E learning cycle model in the experimental class has a moderate influence on the science process skills of students.